Corn Cost-Return Budget in Southeast Kansas - O'Brien, Daniel M.; Shoup, Douglas; Ibendahl, Gregg (My University, 2015)
This publication outlines the expected costs and returns for corn in southeast Kansas.
MF993_2015_04
Keywords: MF993; Economics; Crops; MF